2022
DOI: 10.1101/gr.276126.121
|View full text |Cite
|
Sign up to set email alerts
|

Broad domains of histone marks in the highly compact Paramecium macronuclear genome

Abstract: The unicellular ciliate Paramecium contains a large vegetative macronucleus with several unusual characteristics, including an extremely high coding density and high polyploidy. As macronculear chromatin is devoid of heterochromatin, our study characterizes the functional epigenomic organization necessary for gene regulation and proper Pol II activity. Histone marks (H3K4me3, H3K9ac, H3K27me3) reveal no narrow peaks but broad domains along gene bodies, whereas intergenic regions are devoid of nucleosomes. Our … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
(75 reference statements)
1
6
0
Order By: Relevance
“…loss of H3K9me3 and H3K27me3) are downregulated (Wang et al , 2022). Additionally, Drews et al (2022) reported H3K27me3 to be enriched on highly-expressed genes, all of which are consistent with our current observations. In light of multiple lines of evidence, we believe that these histone marks are not repressive in P. tetraurelia .…”
Section: Discussionsupporting
confidence: 93%
“…loss of H3K9me3 and H3K27me3) are downregulated (Wang et al , 2022). Additionally, Drews et al (2022) reported H3K27me3 to be enriched on highly-expressed genes, all of which are consistent with our current observations. In light of multiple lines of evidence, we believe that these histone marks are not repressive in P. tetraurelia .…”
Section: Discussionsupporting
confidence: 93%
“…Somatic MACs may generally be unable to repress mobile elements by heterochromatinization like germline MICs and other eukaryotic nuclei. In Tetrahymena , most MAC DNA is not associated with classical heterochromatin marks ( 23 ), while in Paramecium MACs, H3K27me3 is not associated with transcription repression, despite being a classic heterochromatin mark in multicellular eukaryotes ( 59 ). In such a permissive expression environment, selection against mobile elements that are not already excised as IESs may be especially effective, unless they are relatively transcriptionally inactive like the Blepharisma retroelements.…”
Section: Discussionmentioning
confidence: 99%
“…Although the classical function of PRC2 complexes is gene repression, there have been reports that EZH2 can function as a transcriptional activator in a PRC2-independent manner ( Kim et al., 2015 , 2018 ; Xu et al., 2012 ). A recent report found the vegetative chromatin landscape of Paramecium to be different from most eukaryotes, and that H3K27me3 accumulates on highly expressed genes, questioning its function as a repressive mark in this system ( Drews et al., 2022 ). Whether Paramecium PRC2 is indeed a transcriptional activator, or if it is an indirect effect, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%